Mighty England do good : culture, faith, empire, and world in the foreign missions of the Church of England, 1850-1915 - Maughan, Steven S., 1962- (Grand Rapids, MI, W.B. Eerdmans Publishing Company, 2014)
In late Victorian and Edwardian England, says Steven Maughan, foreign missions had a broad resonance and significance not adequately explored by historians of English culture. Mighty England Do Good fills that lacuna by examining the rapid growth of foreign missions in the Church of England between 1850 and 1915, culminating at the height of the missionary enterprise in Britain. Maughan's book bridges the gaps between religious, cultural, and imperial history to give a full picture of the movement's importance. Maughan explores Anglicanism as a microcosm of the larger religious culture of Britain, particularly in light of the expanding British empire. This book provides a multidimensional reassessment of the power that foreign missions had to shape belief, institutions, culture, and practice not only within the Church of England but also in the broader culture of the time.
The foreign missions of the Church of England : reconceptualizing Anglicanism in imperial culture, 1850-1915 -- Faith, authority, and the sectarian spirit of Anglican foreign missions -- Revivalism and church order : late Victorian Anglican missionary expansion -- Women's work : expanding the home in the kingdom of God -- Anglicans and education : university culture and the professionalization of conversion -- Ideals of church revival : Christian communalism and the high church bid for Anglican unity -- Women's work : leadership, dependence, and the limits of change -- Edwardian challenges and the collapse of an Anglican greater Britain -- Conclusion.
Includes bibliographical references (pages 473-501) and index.
Keywords: Church of England -- Missions -- History -- 19th century; Church of England -- Missions -- History -- 20th century